Any Woman's Blues: A Critical Overview of Women, Crime, and the Criminal Justice System - Klein, Dorie (Social justice, 2013)
The article presents key elements critical to a radical view of the phenomenon of female crime and experience with the criminal justice system. Topics discussed include a critique on traditional and criminological literature on women, a description of how the scholarship was used in the formulation of criminal justice planning and the basic tenets of radical criminology and the position of the women in contemporary American society and the criminal justice system as an instrument of control.